54 Delivering system transformation and efficiency in sexual and reproductive health through online services. (31st October 2017) - Holdsworth, G; Howroyd, C; Parry, G; Clune, M; Sa, J de; Black, A; Baraitser, P
Abstract : Regular testing and rapid treatment for sexually transmitted infections (STIs) are important strategies for control. – Lambeth and Southwark are London boroughs with high rates of STI prevalence. Sexual health services provide excellent clinical care but demand outstrips capacity. SH:24 (www.sh24.org.uk) is a collaboration of designers, public health and clinicians working to develop and scale solutions to improve access to services. SH:24 has pioneered online sexual and reproductive health services, delivered in partnership with the NHS and developed using Government Digital Service principles. SH:24 provides free access to online sexual health testing and results within 72 hours, online contraception, postal chlamydia treatment, clinical information, support and advice SH:24 worked extensively with users and clinical teams to design the service and ensure seamless integration with clinics. – – – A multi-sector advisory board guided implementation and ensured service transformation was embedded organisationally across the boroughs. The service continually seeks feedback from staff and users and optimises as part of agile methodology – 'build test learn'. A randomised controlled trial showed the online service doubled uptake of STI testing (RR 1.87, p<0.0001); irrespective of gender, sexuality, ethnicity, deprivation level and age (16–30 years). A new clinic triage pathway for asymptomatic users reduced simple STI testing from 17% to 12% while complex activity increased from 69%–75%. The user feedback survey consistently measures satisfaction at 4.94 out of 5 and the service has won multiple awards including BMJ innovation team of the year. SH:24 reflects the NHS strategy on digital care to meet expanding demand within limited resources. – Going 'digital' chimes with a radical upgrade in prevention and public health – making access easier, diagnosis and treatment faster – and allowing patients to gain greater control of their own care.